Análisis de sentimientos sobre la percepción ciudadana de la vacunación del COVID-19 en Colombia (2021)
In this degree work, a sentiment analysis of the perception of COVID-19 vaccination in Colombia is carried out, taking as a source of data the publications on the social network Twitter. With the activities carried out, it was possible to obtain information on the Tweets from March 15 to April 25, 2021 through the streaming API provided by the social network, the information was stored in MongoDB databases in the cloud. Python was used as a programming language for the implementation of the source code by creating notebooks.